PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP LOYALITAS KARYAWAN (STUDI KASUS PADA KARYAWAN PT. X YANG BEKERJA DI CUSTOMER PRODUCT DIVISION) - Lana Afril Andinni; Paulina Harun (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to examine the effect of work environment, workload, and motivation on job satisfaction and its effect on employee loyalty. The sample used in this research is 200 employees of PT. X in customer product division. The data collection technique used was a survey in the form of questionnaires made on the Google From and distributed online to employees of PT. X in customer product division. The data analysis method used in this research is structural equation model analysis (SEM) and processed using the AMOS 23 application. The result of the analysis using SEM show that, the work environment has a positive but not significant effect on job satisfaction, the work environment has a positive and significant influence on employee loyalty, workload has a positive (not negative) and significant effect on job satisfaction, workload has a positive (not negative) and not significant on employee loyalty, motivation has a positive and significant effect on job satisfaction, motivation has a positive and significant effect on employee loyalty, job satisfaction has a positive and significant effect on employee loyalty, job satisfaction cannot mediate the relationship between work environment and employee loyalty, job satisfaction cannot mediate the relationship between workload and employee loyalty, job satisfaction mediates the relationship between motivation and employee loyalty.